DEVELOPING SUPPLEMENTARY ENGLISH TEACHING MATERIALS FOR THE TENTH YEAR STUDENTS OF SMA PGRI 6 DENPASAR IN IMPLEMENTING CURRICULUM 2013 - YUNIARI, NI MADE (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2016)
AbstractThe aim of this study is to develop the supplementary English teaching materials for the tenth year students of SMA PGRI 6 Denpasar in implementing Curriculum 2013. In this study, the model of Research and Development by Sugiono was employed as the research procedures. From those procedures, new materials were developed, analyzed by experts, revised, field-tested, analyzed, and finally produced. The data were collected by using several instruments namely rubric and questionnaire which was taken from the criteria of a good material by Tomlinson and BSNP. The rubric was filled by the expert judgments and teacher, while the questionnaire was filled by teacher and students. In addition, the pretest and posttest were also conducted. The result of pretestâ??s mean score was 79.08. Then the mean score of posttest was 86.58. It shows that the result of posttestâ??s mean score is higher than pretestâ??s mean score. The result of this study shows that the supplementary English teaching materials which was developed by researcher is effective to be used for teaching English in implementing curriculum 2013. In conclusion, the supplementary English teaching materials are suitable to be used for the tenth year students of SMA PGRI 6 Denpasar in implementing curriculum 2013.Key words: Supplementary, English Teaching Materials, Curriculum 2013Â AbstrakPenelitian ini bertujuan untuk mengembangkan materi pelengkap pengajaran Bahasa Inggris untuk siswa kelas sepuluh SMA PGRI 6 Denpasar dalam mengimplementasikan Kurikulum 2013. Pada penelitian ini, Model Penelitian dan Pengembangan dari Sugiono dipakai sebagai prosedur penelitian. Dari prosedur-prosedur tersebut, materi-materi baru dikembangkan, dianalisa oleh para ahli, direvisi, di tes di lapangan, dianalisa, dan terakhir diproduksi. Data dikumpulkan dengan menggunakan beberapa instrument yang bernama rubric dan kuesioner yang diambil dari Kriteria materi yang baik berdasarkan Tomlinson and BSNP. Rubrik tersebut diisi oleh pakar ahli dan guru, sedangkan kuesioner diisi olehguru dan siswa. Selain itu, juga diadakan pretest dan posttest. Hasil skor mean dari prestest adalah 79.08, sedangkan skor mean dari posttest adalah 86.58. Ini menunjukkan bahwa hasil skor mean dari posttest lebih tinggi dari skor mean pretest. Hasil dari penelitian ini menunjukkan bahwa materi pelengkap pengajaran Bahasa Inggris yang dikembangkan oleh peneliti efektif digunakan untuk mengajar Bahasa Inggris dalam pengimplementasian Kurikulum 2013. Dapat disimpulkan bahwa materi pelengkap pengajaran Bahasa Inggris ini cocok digunakan untuk siswa kelas sepuluh SMA PGRI 6 Denpasar dalam mengimplementasikan Kurikulum 2013.Kata Kunci: Pelengkap, Materi Pengajaran Bahasa Inggris, Kurikulum 2013.Â